2004
DOI: 10.2174/1381612043386374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Development of Microbicides for the Prevention of HIV Infection

Abstract: The HIV/AIDS pandemic continues its spread at a rate of over 15,000 new infections every day. Sexual transmission of HIV-1 is the dominant mode of this pandemic spread. For the first time since the disease emerged in the early 1980s, about half the 42 million people now living with HIV/AIDS worldwide are women. Worldwide, more than 90 percent of all adolescent and adult HIV infections have resulted from heterosexual intercourse. The "feminization" of the pandemic largely driven by the social, economic, and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
102
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 0 publications
0
102
0
2
Order By: Relevance
“…They are currently considered to be one of the most promising biomedical interventions for preventing heterosexual transmission. Because the majority of the ϳ3 million HIV infections that occur each year are in women (4,5), effective female-initiated prevention methods are urgently needed. Second-generation microbicides, containing antiretrovirals (ARVs), are now being tested for efficacy in phase III clinical trials [supporting information (SI) Table S1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are currently considered to be one of the most promising biomedical interventions for preventing heterosexual transmission. Because the majority of the ϳ3 million HIV infections that occur each year are in women (4,5), effective female-initiated prevention methods are urgently needed. Second-generation microbicides, containing antiretrovirals (ARVs), are now being tested for efficacy in phase III clinical trials [supporting information (SI) Table S1].…”
mentioning
confidence: 99%
“…This will be closely followed by a microbicide containing dapivirine, which belongs to the nonnucleoside reverse transcriptase inhibitor (NNRTI) class of ARVs (6); trial results will be available in 2010. Three other ARV-based microbicides, containing NNRTIs, are in earlier-phase trials (3,5,(7)(8)(9)(10). ARV-based microbicides are anticipated to be highly effective; however, there is concern that, if used by HIV-positive women, class-specific drug resistance may emerge.…”
mentioning
confidence: 99%
“…Our data demonstrated that PAs can be effective if applied directly to the site of virus replication, in this case the respiratory system for viral pneumonia. Recent advances in the design and modification of PAs have reduced toxicity, and several anionic polymers are now in clinical trials as topical and therapeutic antiviral agents against HIV infection (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…However, initial clinical studies evaluating OTC spermicides as potential microbicides had mixed results [21][22][23][24] and were eventually abandoned with the disappointing results from the COL-1492 study, showing that the OTC spermicide nonoxynol-9 (N-9) could be toxic to the vaginal tissue thereby increasing the risk of HIV infection [25]. There are other candidate microbicides currently in clinical trials that might demonstrate dual protection [26][27][28][29][30]. However, none of the products are proven contraceptives.…”
Section: Discussionmentioning
confidence: 99%